Endoscopically Assisted Modified Caldwell-Luc Approach to Enucleation of Dentigerous Cyst With Ectopic Tooth From the Maxillary Sinus. Issue 6 (September 2018) - Liau, Isaac; Lynch, Nicholas; Hearn, Brenton; Cheng, Andrew
Abstract : Abstract: Dentigerous cysts in the craniomaxillofacial complex are a benign pathology commonly associated with ectopically placed teeth. Owing to slow and asymptomatic growth, they often attain considerable size before diagnosis that may compromise adjacent anatomical structures. Various techniques for removal of dentigerous cysts from the maxillary sinus have been described. This case report demonstrates a hybrid endoscopically assisted modification of the Caldwell-Luc approach to provide the technical advantages of both techniques